'Amit, wake up': indigenization, gender and Taiwanese pop star Chang Hui-mei's music. Issue 4 (3rd July 2020) - Gao, Yuan
ABSTRACT: This article analyses the reinvention of the indigenous identity combined with gender critique in contemporary Taiwan. In particular, I focus on Chang Hui-mei, the most famous Taiwanese pop star with an indigenous origin. A Puyuma native, Chang released two experimental studio albums entitled with her indigenous name Amit in 2009 and 2015. One theme that these albums explore is gender politics, including feminist critique on heteropatriarchy and celebration of queer sexualities. Chang's intervention in gender norms has made her an iconic figure in Taiwan's LGBTQ activism. Such engagement allows her to re-establish a new indigenous identity that goes beyond the essentialist idea of being indigenous. Drawing on James Clifford's theory of becoming indigenous in the twenty-first century, I offer close readings of Chang's song lyrics, music videos and live performance. In these music products, Chang draws people's attention to the subversive images of women and the affective intimacy between gay men and straight women. Her live performance has advocated the public display of queer affection, by which a queer utopia is constructed to facilitate queer communal bond. Chang revises the mainstream imagination of being indigenous that connotes 'primitivism', thus illuminating alternative ways to claim ethnic and gender subjectivity.